2023
DOI: 10.1097/jnr.0000000000000577
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Among Workplace Burnout, Resilience, and Well-Being in Nursing Staff: A Cross-Sectional Study in Taiwan

Shau-Tion TZENG,
Bei-Yi SU,
Hsiao-Mei CHEN

Abstract: Background Because nurses often work in medical environments characterized by high workloads and high levels of stress and pressure, they are particularly vulnerable to workplace burnout and their well-being may suffer. Related studies on burnout, resilience, and well-being have focused primarily on teachers, social workers, and students, with few studies addressing the situation faced by nursing staff. It is important to understand the factors affecting the well-being of nursing staff. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…In Taiwan, perhaps via the influence of traditional Confucian culture, raising children is considered a responsibility and source of happiness. This also seems to echo the findings of Tzeng et al (2023), who noted nurses with more than three children reported greater self-affirmation and well-being than their childless peers. This issue deserves to be explored further in future empirical research.…”
Section: Discussionsupporting
confidence: 78%
“…In Taiwan, perhaps via the influence of traditional Confucian culture, raising children is considered a responsibility and source of happiness. This also seems to echo the findings of Tzeng et al (2023), who noted nurses with more than three children reported greater self-affirmation and well-being than their childless peers. This issue deserves to be explored further in future empirical research.…”
Section: Discussionsupporting
confidence: 78%